Data from: Evaluating tooth strontium and barium as indicators of weaning age in Pacific walruses ... - Clark, Casey; Horstmann, Lara; Misarti, Nicole (Dryad, 2020)
A dataset of calcium-normalized 88Sr and 137Ba concentrations from laser ablation transects across the cementum layer of 107 (female: n = 84, male: n = 23) Pacific walrus (Odobenus rosmarus divergens) teeth. Dataset includes spreadsheets containing elapsed time of laser ablation transect in seconds (ElapsedTime_s; laser transect speed = 5μm/s), calcium-normalized strontium concentrations (Sr_ppm_m88; values below limit of detection replaced with 1/2*limit of detection, see methods), and calcium-normalized barium concentrations (Ba_ppm_m137; values below limit of detection replaced with 0.5*limit of detection). Photos (in .tif format) of tooth cementum used to estimate the positions of cementum growth layer groups are included for each animal. For teeth where more than one laser ablation scar is visible in the photo, an arrow is included to indicate the laser ablation scar that corresponds with the included trace element data. Finally, a Word document containing metadata (Catalog Number/ID, Sex, Median Age ... : Trace element analysis and data processing Walrus teeth used for this study (female: n = 84, male: n = 23) were on loan from the University of Alaska Museum in Fairbanks, Alaska, the National Museum of Natural History, Smithsonian Institution, in Washington DC, and the Alaska Department of Fish & Game. These specimens each represented an individual animal, and were collected at various locations throughout the Pacific walrus range in the Bering and Chukchi seas. Most teeth originated from Alaska Native subsistence harvests, though a small number came from research expeditions. Dates of collection ranged from 1932 to 2016. In preparation for analysis, teeth were sectioned longitudinally using a slow-speed, water-cooled saw equipped with a diamond blade, creating a cross section of the center of the tooth with a thickness of ~1.5mm. This cross section was then polished using a rotary polishing wheel with a 3000 grit smoothing disc, rinsed with ultrapure water, and allowed to dry. Specimens were rinsed and ...